Newsminer: um sistema de data warehouse baseado em texto de notícias - Nogueira, Rodrigo Ramos (2017)
Data and text mining applications managing Web data have been the subject of recent research. In every case, data mining tasks need to work on clean, consistent, and integrated data for obtaining the best results. Thus, Data Warehouse environments are a valuable source of clean, integrated data for data mining applications. Data Warehouse technology has evolved to retrieve and process data from the Web. In particular, news websites are rich sources that can compose a linguistic corpus. By inserting corpus into a Data Warehousing environment, applications can take advantage of the flexibility that a multidimensional model and OLAP operations provide. Among the benefits are the navigation through the data, the selection of the part of the data considered relevant, data analysis at different levels of abstraction, and aggregation, disaggregation, rotation and filtering over any set of data. This paper presents Newsminer, a data warehouse environment, which provides a consistent and clean set of texts in the form of a multidimensional corpus for consumption by external applications and users. The proposal includes an architecture that integrates the gathering of news in real time, a semantic enrichment module as part of the ETL stage, which adds semantic properties to the data such as news category and POS-tagging annotation and the access to data cubes for consumption by applications and users. Two experiments were performed. The first experiment selects the best news classifier for the semantic enrichment module. The statistical analysis of the results indicated that the Perceptron classifier achieved the best results of F-measure, with a good result of computational time. The second experiment collected data to evaluate real-time news preprocessing. For the data set collected, the results indicated that it is possible to achieve online processing time.